PEMILIHAN DAN PENGANGKATAN KEPALADESA TANJUNG MUARA YANG BERADA PADASEL DI BENGKULU UTARA DITINJAU DARIUNDANG – UNDANG NO. 6 TAHUN 2014TENTANG DESA: The Election and Appointment of Tanjung Muara Village Head North Bengkulu Reviewed from Act No. 6 Of 2014 - Andrea Maraya Salsabila; Wiratno (Reformasi Hukum Trisakti, 2024)
The election and appointment of the Village Head in Tanjung Muara Village were conducted in a prison cell because the elected Village Head was charged with corruption. The problem formulation in this article is how the implementation of the election and appointment of the Village Head of Tanjung Muara, North Bengkulu was carried out and whether the implementation was in accordance with the Village Head Election Regulations. This study uses a Normative Method, which aims to describe the research object and utilizes Secondary Data processed qualitatively and concluded deductively. The discussion results show that although the village head election was conducted according to the applicable regulations, the corruption case involving the elected village head created legal obstacles. The legal issues arising from the corruption case affected the election process, but legal procedures were still followed to ensure legal certainty. In conclusion although the election and appointment process complied with the regulations, the legal issues faced by the elected village head impacted the implementation and necessitated the appointment of an interim acting official.